PELATIHAN PEMBUATAN SABUN CAIR CUCI PIRING UPAYA MENINGKATKAN MOTIVASI BELAJAR SISWA SMAN 30 GARUT - Alawiyah, Aika (Universitas Trisakti, 2024)
Senior High School 30 (SMAN 30) in Garut is a school that benchmarks the quality of education in the southern region of West Java. Some students at SMAN 30 Garut still find it challenging to learn chemistry, which tends to be less related to daily life, so chemistry is less prevalent. The applied chemistry practical implementation activity was carried out to improve students' learning and motivation at SMAN 30 Garut. The training on making dishwashing liquid soap is expected to equip students with the knowledge and competencies to make simple and valuable products. The method used in this activity is exposure and training (direct practice) for making dishwashing liquid soap. The results obtained are dishwashing liquid soap that has been packaged and can be distributed to the public. The students played an active role and enthusiastically participated in the training activities. The knowledge gained regarding the chemicals used in soap making can be put into practice by themselves by adding creative ideas to develop product innovation